Next gen PhD : a guide to career paths in science - Sinche, Melanie V. (Harvard University Press, 2016)
An upper-level degree is a prized asset in the eyes of many employers, and nonfaculty careers once considered Plan B are now preferred by the majority of science degree holders. Melanie Sinche profiles science PhDs across a wide range of disciplines who share proven strategies for landing a rewarding occupation inside or outside the university.--